P-216 How hospices can add value to the delivery of local sustainability and transformation plans (STP). Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Webb, Michelle; McConville, Rebecca; Bareham, Kerry
Abstract : Frailty is recognised as a long term condition. However, the syndromes of frailty are often viewed by older people, professionals and society alike as an inevitable part of aging. As a consequence, opportunities are missed to identify people's underlying complex needs including palliative and end of life care needs. This results in people with frailty, often presenting in crisis to health services with conditions that ostensibly appear to have been avoidable. Lincolnshire has implemented Neighbourhood Team working, underpinned by the principles of the 'House of Care' (HoC) policy: a proactive model of self-care that encourages a move away from the traditional health care delivery model that is single condition specific to one that has a person-centred approach and promotes an integrated model of care. A model that is familiar to providers of specialist palliative and end of life care. Therefore, St Barnabas Lincolnshire Hospice has worked collaboratively with the members of the Neighbourhood Teams to develop a Frailty Pathway to inform the Neighbourhood Teams priorities. The Frailty Pathway works as a boundary object to facilitate a whole systems approach by the Neighbourhood Teams, thus ensuring people with frailty, wherever they present are able to have their needs recognised, and assessed resulting in personal support and care plans reflecting their outcomes including when appropriate, advance care planning and timely access to palliative and end of life care. We would like to present our experiences in collaboration with a Neighbourhood Team Lead, to share how hospices can support generalists to improve the health and well-being outcomes for people with multi-comorbidity and frailty, by widening access to palliative and end of life care. Thus enabling people to achieve person-centred outcomes including, preferred place of care, and supporting the STP aspiration of reducing avoidable admissions by 30%.